Narrrative Imagination as a Problem of Ethics - Gelūnas, Benediktas; Sabolius, Kristupas (Problemos, 2015)
In this paper it is proposed that narrative imagination is a necessary condition of ethics for three main reasons: the syntheses of narrative self-identity, narrative Other, and narrative common world. The context of the analysis is constituted by the phenomenological understanding of imagination as an intentional activity of consciousness, the Aristotelian link between poeisis and praxis, and the hermeneutical treatment of narrative as a fundamental structure of understanding. Relying mostly on the works of Richard Kearney, this article considers implicitly and explicitly ethical aspects of narrativity, and also narrative ethics as a midway position between relativism and absolutism.